2021
DOI: 10.1080/19490976.2021.1887722
|View full text |Cite
|
Sign up to set email alerts
|

Integrated gut virome and bacteriome dynamics in COVID-19 patients

Abstract: SARS-CoV-2 is the cause of the current global pandemic of COVID-19; this virus infects multiple organs, such as the lungs and gastrointestinal tract. The microbiome in these organs, including the bacteriome and virome, responds to infection and might also influence disease progression and treatment outcome. In a cohort of 13 COVID-19 patients in Beijing, China, we observed that the gut virome and bacteriome in the COVID-19 patients were notably different from those of five healthy controls. We identified a bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
163
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(187 citation statements)
references
References 63 publications
20
163
4
Order By: Relevance
“…2F and G ), further suggesting that microbial change is virus dose dependent. A similar relationship was previously observed among unvaccinated and vaccinated SARS-CoV-2-infected mice with a high dose ( 47 ). Analyzing the commensal microbiome in other diseases has shown that the microbiota can both regulate and be regulated by viral pathogens and facilitate stimulatory or suppressive effects on the host immune response ( 49 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…2F and G ), further suggesting that microbial change is virus dose dependent. A similar relationship was previously observed among unvaccinated and vaccinated SARS-CoV-2-infected mice with a high dose ( 47 ). Analyzing the commensal microbiome in other diseases has shown that the microbiota can both regulate and be regulated by viral pathogens and facilitate stimulatory or suppressive effects on the host immune response ( 49 ).…”
Section: Discussionsupporting
confidence: 86%
“…These observations suggest a virus dose-dependent effect of the ceca microbial alpha diversity in mice infected with SARS-CoV-2. While preparing the manuscript, a report was published that analyzed the small intestine microbiome of hACE2 mice among unvaccinated and vaccinated mice challenged with a high dose of SARS-CoV-2 ( 47 ). While we compared control mice to nonvaccinated mice challenged with low and high doses of SARS-CoV-2 in this study, findings were similar, since a decrease in alpha diversity in the unvaccinated mice was reported, which was consistent with results obtained from human fecal samples ( 5 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, COVID-19 infection enriches the opportunistic pathogens and lessens the populations commonly known as beneficial. Depletion in some bacterial groups, such as Faecalibacterium prausnitzii, Eubacterium rectale , and Collinsella aerofaciens were even higher in the COVID-19 patients using antibiotics during treatment, with a lower bacterial diversity ( Zuo et al., 2020 ; Cao et al., 2021 ; Yeoh et al., 2021 ). Alteration in the gut microbiota have been reported to be associated with COVID-19 severity and some of the populations, such as Faecalibacterium were negatively correlated with the disease severity while some of them, such as Coprobacillus correlated positively ( Zuo et al., 2020 ; Cao et al., 2021 ; Yeoh et al., 2021 ).…”
Section: Possible Link Between Gut Dysbiosis and Covid-19mentioning
confidence: 94%
“…Depletion in some bacterial groups, such as Faecalibacterium prausnitzii, Eubacterium rectale , and Collinsella aerofaciens were even higher in the COVID-19 patients using antibiotics during treatment, with a lower bacterial diversity ( Zuo et al., 2020 ; Cao et al., 2021 ; Yeoh et al., 2021 ). Alteration in the gut microbiota have been reported to be associated with COVID-19 severity and some of the populations, such as Faecalibacterium were negatively correlated with the disease severity while some of them, such as Coprobacillus correlated positively ( Zuo et al., 2020 ; Cao et al., 2021 ; Yeoh et al., 2021 ). The severity of COVID-19 patients has been determined with an elevated level of inflammatory cytokines in blood or feces including IL-18, IL-10, TNF-α, C- X- C motif ligand (CXCL)8 and CXCL10, blood markers such as C reactive protein (CRP), lactate dehydrogenase, and natural killer cells ( Tang et al., 2020 ; Tao et al., 2020 ; Yeoh et al., 2021 ).…”
Section: Possible Link Between Gut Dysbiosis and Covid-19mentioning
confidence: 94%